Pre employment bootcamp module: UiTM Cawangan Sarawak / Puan Dayang Nordiana Awang Othman and Dr. Azlina Bujang - Awang Othman, Dayang Nordiana; Bujang, Azlina (Universiti Teknologi MARA, Sarawak, 2025)
Some recent grads struggle to express themselves verbally and in writing. They are unaware of their own tremendous potential, abilities, qualities, competences, values, attributes, and traits, which may be turned into words, phrases, or sentences, whether written or spoken, particularly while writing a CV, cover letter, and attending a job interview. When looking for or getting a job, employers must be able to detect the distinguishing characteristics that set them apart from others. They must be able to pitch or promote the strengths in a way that will impress prospective employers and make them choose the suitable one. For kickstart, knowing oneself in depth allows you to generate fundamental career-related facts about yourself, as well as how to match that personal information with appropriate positions and make yourself marketable. There are various approaches for obtaining accurate information about yourself, including SWOT analysis, personality tests, self-assessment checklists, peer feedback, self-reflection, and group work.